(untitled) (Journal of Pharmaceutical Negative Results, 2022)
AIMS: Evaluation the effect of incorporation of different concentration (1.5% and 2.5% by volume) of virgin coconut oil to heat cure acrylic soft denture lining material on thermal conductivity, and tensile strength.Material and method: Sixty specimens of heat cure acrylic soft denture lining materials. The specimens were divided into two major groups according to the tests (30 for Thermal conductivity test, and 30 for Tensile strength test). Each group was sub divided into three minor groups, (10) specimens of heat cure acrylic soft denture lining materials without any incorporation (control group), (10) specimens of heat cure acrylic soft denture lining materials with incorporation of 1.5 % virgin coconut oil, and (10) specimens of heat cure acrylic soft denture lining materials with incorporation of 2.5 % virgin coconut oil. Thermal conductivity specimens were fabricated with dimensions of (40 mm diameter × 2.5 mm thickness), also The (Lee disc) Technologies, Department equipment was used to evaluate thermal conductivity test. Tensile strength specimens were fabricated with dimensions of (80mmx9mmx 3mm) for (length, width, and thickness), also the Universal Instron testing machine was used to evaluate the tensile strength test.Result: Data statically analyzed by One-way ANOVA and LSD tests. The results of thermal conductivity tests was showed highly significant differences at P<0.01. At the same time the tensile strength test showed the highly significant differences at P<0.01 in the all studies groups.Conclusion: The incorporating of 2.5% of virgin coconut oil into heat cure acrylic soft denture lining material causes increases of thermal conductivity, and increases of tensile strength.